2014
DOI: 10.1088/0957-4484/25/26/265701
|View full text |Cite
|
Sign up to set email alerts
|

Graphene supported plasmonic photocatalyst for hydrogen evolution in photocatalytic water splitting

Abstract: It is well known that the noble metal nanoparticles show active absorption in the visible region because of the existence of the unique feature known as surface plasmon resonance (SPR). Here we report the effect of plasmonic Au nanoparticles on the enhancement of the renewable hydrogen (H2) evolution through photocatalytic water splitting. The plasmonic Au/graphene/TiO2 photocatalyst was synthesized in two steps: first the graphene/TiO2 nanocomposites were developed by the hydrothermal decomposition process; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 80 publications
1
48
0
Order By: Relevance
“…However, the Drifts-FTIR spectrum of OGNs (Fig. 6b) has the adsorption bands centered at wave numbers that resemble those mentioned in the previous works [35][36][37][38][39] with the band at *1073 cm -1 attributed to C-O epoxy stretching vibrations, *1224 cm -1 due to C-OH stretching vibrations, *1623 cm -1 from deformation vibration of water molecules, *1734 cm -1 from C=O carbonyl stretching and *3613 cm -1 from stretching vibration of hydroxyl groups. Thus, the GNs have been oxidized extensively, and the surface has been decorated with aforementioned carbonyl, epoxy and hydroxyl functional groups.…”
Section: Resultssupporting
confidence: 78%
“…However, the Drifts-FTIR spectrum of OGNs (Fig. 6b) has the adsorption bands centered at wave numbers that resemble those mentioned in the previous works [35][36][37][38][39] with the band at *1073 cm -1 attributed to C-O epoxy stretching vibrations, *1224 cm -1 due to C-OH stretching vibrations, *1623 cm -1 from deformation vibration of water molecules, *1734 cm -1 from C=O carbonyl stretching and *3613 cm -1 from stretching vibration of hydroxyl groups. Thus, the GNs have been oxidized extensively, and the surface has been decorated with aforementioned carbonyl, epoxy and hydroxyl functional groups.…”
Section: Resultssupporting
confidence: 78%
“…Singh etc. synthesized graphene supported plasmonic photocatalyst for hydrogen production and proved that graphene acted as an electron acceptor to suppress the recombination of charge carriers [21]. Dubale and co-workers reported that graphene exhibited synergetic effect with Cu 2 O in enhancing the absorbance of the visible light, separating the charge carriers and suppressing the photocorrosion [22].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9 shows the Raman spectra of the Au@TiO 2 -P25 catalysts. Singh et al (2014) reported that anatase phase shows major bands at ~150, 395, 515 and 638 cm −1 . These bands can be appreciated in all the TiO 2 -P25 catalysts and have been attributed to the five Raman-active modes of the anatase phase, corresponding to E g(1) , B 1g(1) , A 1g + B 1g(2) and E g (2) vibrational modes.…”
Section: Characterization Of the Au@tio 2 Catalystsmentioning
confidence: 99%
“…These bands can be appreciated in all the TiO 2 -P25 catalysts and have been attributed to the five Raman-active modes of the anatase phase, corresponding to E g(1) , B 1g(1) , A 1g + B 1g(2) and E g (2) vibrational modes. The typical Raman bands resulting from the rutile phase appear at ~143 (superimposed with the 145 cm −1 band from the anatase), 235, 455 and 612 cm −1 and can be ascribed to the B 1g , E g and A 1g vibrational modes (Singh et al, 2014;Wang et al, 2012). Only the peak at ca.…”
Section: Characterization Of the Au@tio 2 Catalystsmentioning
confidence: 99%